Designing organizational eco-map to develop a customer value proposition for a "slow tourism" destination - Andrejs Čirjevskis (Administrative Sciences, 2019)
Despite the widespread agreement on the importance of customer value proposition (CVP) as one of the most critical aspects of business models (BM), little is known about how strategically valuable organizational resources may contribute to the transformation of CVP. This paper aims to develop and to test a new research framework: The organizational eco-map to explore how strategically valuable resources are underpinning a new customer value proposition of a focal company. Customer value proposition hence is an encapsulation of a strategic management decision on what the company believes its customers value the most and what it can deliver in a way that gives it a competitive advantage. Being a research-based paper, the topic is approached by theoretical analysis, conceptual development, and empirical justification. The presented organizational eco-map model encourages practitioners to grasp an exact relationship between strategically valuable resources of the organization and customer value proposition. Empirically, the paper examines the role of Latvian cultural resources in the forthcoming transformation of the customer value proposition for Riga Central Market of Latvia, a huge infrastructural establishment. Therefore, marketing practitioners will find new ways of understanding customers' value creation for a "slow tourism" destination to develop marketing strategies to engage cultural resources of suppliers with their customers' consumption processes to enhance better customer satisfaction.
Keywords: 350; business model; customer value proposition; organizational eco-map; cultural resources; slow tourism